PERUMUSAN STRATEGI BERSAING UNTUK MENINGKATKAN KEUNGGULAN PERSAINGAN PADA INTERNET CAFE Studi Kasus pada Platinum Internet Cafe Yogyakarta - , Neng Titoh Siti Hapsoh, Prof. Lincolin Arsyad, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aims to study the external environment and the internal structure of the market in the internet cafe service industry in Yogyakarta, by analyzing the internet café services industry through a SWOT analysis, five forces, driving forces, competitive advantages, key success factors and the formulation of strategies competitive matches in the face of competition in service industries internet café in the future. Understanding of the relationship between external and internal environment is the key to success in formulating a strategy created by the drafters of the strategy. The results indicate that the service industry internet café located in a growing industry and the matching strategy used by companies that compete according to the strategy of differentiation. From the analysis of the company can know its position in the competition as well as what will be achieved in the foreseeable future. To achieve the company's desire should be considered to determine the most appropriate strategy to be applied. Within this thesis the author offers a generic strategy of differentiation is supported by the improved quality of service.